Cow’s Milk Allergy or Gastroesophageal Reflux Disease—Can We Solve the Dilemma in Infants? - Salvatore, Silvia (Nutrients, 2021)
Cow’s milk allergy (CMA) and gastro-esophageal reflux disease (GERD) may manifest with similar symptoms in infants making the diagnosis challenging. While immediate reaction to cow’s milk protein indicate CMA, regurgitation, vomiting, crying, fussiness, poor appetite, sleep disturbances have been reported in both CMA and GERD and in other conditions such as functional gastrointestinal disorders, eosinophilic esophagitis, anatomic abnormalities, metabolic and neurological diseases. Gastrointestinal manifestations of CMA are often non-IgE mediated and clinical response to cow’s milk free diet is not a proof of immune system involvement. Neither for non-IgE CMA nor for GERD there is a specific symptom or diagnostic test. Oral food challenge, esophageal pH impedance and endoscopy are recommended investigations for a correct clinical classification but they are not always feasible in all infants. As a consequence of the diagnostic difficulty, both over- and under- diagnosis of CMA or GERD may occur. Quite frequently acid inhibitors are empirically started. The aim of this review is to critically update the current knowledge of both conditions during infancy. A practical stepwise approach is proposed to help health care providers to manage infants presenting with persistent regurgitation, vomiting, crying or distress and to solve the clinical dilemma between GERD or CMA.